Successful Endoscopic Resection of Gastric Mucosa-Associated Lymphoid Tissue Lymphoma Unresponsive to Helicobacter pylori Eradication Therapy - Choi, Jeongmin (Clinical endoscopy, 2022)
Eradication of Helicobacter pylori is the first-line treatment for gastric mucosa-associated lymphoid tissue (MALT) lymphomas; however, lesions may persist in 20% of patients after initial treatment, thereby necessitating the use of an additional therapeutic approach. Other treatment options include radiation therapy, chemotherapy, endoscopic resection, rituximab therapy, or watchful waiting. We present a case of localized gastric MALT lymphoma that did not respond to H. pylori eradication therapy. The patient waited for 12 months but the tumor showed no signs of regression endoscopically. Histologic examination revealed residual MALT lymphoma. The tumor was then successfully treated using endoscopic submucosal dissection and the patient remained disease-free for 4 years. To our knowledge, this is the first case in which a gastric MALT lymphoma was treated with endoscopic submucosal dissection. In conclusion, endoscopic resection may be recommended as second-line therapy for properly selected patients with gastric MALT lymphoma as it is effective and minimally invasive.